2013
DOI: 10.1590/0004-282x20130130
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cavernous angioma complicated by hemorrhage: susceptibility-weighted imaging findings

Abstract: A 16-year-old boy presented with posterior cervical pain radiating to the right upper limb. Cervical magnetic resonance imaging (MRI) revealed an intramedullary cavernous angioma (CA) in the level of C2. Susceptibility-weighted ima ging (SWI) showed longitudinal hypointensity from the bulb to the level of T1, which was suggestive of a longitudinal fiber-dissecting hemorrhage ( Figure).Intramedullary CAs are associated with an increased risk of hemorrhage. SWI is optimized for detection of magnetic susceptibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…It has been reported that ESWAN is a precise method to show the intracranial capillary telangiectasia and cerebral hemorrhage (13). It can be used not only to diagnose the hemangioma subtypes of the brain or spine, but also to directly display the vessels in cartilage tube or disease progression (14)(15)(16)(17). However, there is no report of ESWAN being used for the diagnosis of IMHs.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that ESWAN is a precise method to show the intracranial capillary telangiectasia and cerebral hemorrhage (13). It can be used not only to diagnose the hemangioma subtypes of the brain or spine, but also to directly display the vessels in cartilage tube or disease progression (14)(15)(16)(17). However, there is no report of ESWAN being used for the diagnosis of IMHs.…”
Section: Introductionmentioning
confidence: 99%